Protecting National Security and Economic Freedom - Busari, Arfiah; Hasid, Zamruddin; Jiuhardi, Jiuhardi (Intermestic: Journal of International Studies; Vol 7 No 2 (2023)DO - 10.24198/intermestic.v7n2.7, 2023)
This paper takes the initiative to study the causality between military spending (MS), GDP of military sector (GMS), armed forces personnel (AFP), arms exports (AE), and arms imports (AI) and economic freedom (FE). Objectivity is determined in Indonesia–Malaysia–Singapore. Panel data regression is using to test a series of hypotheses over the period 2014–2021. Furthermore, the probability parameter applied is ? <0.05. Various conclusions show that there are differences in the three observations. First, AFP and AE have a significant effect on EF in Indonesia. Second, MS, GMS, and AI actually affect EF in Malaysia significantly. Third, MS, GMS, and AFP have significant links to EF in Singapore. The results of the investigation provide useful insights into the progress of the military industry and weapons technology, thereby bringing about a more progressive economic escalation. Economic freedom as an identity that symbolizes the maturity of a country's prosperity. Therefore, peace is difficult to achieve if the demands to fight for prosperity are not carried out.